A case of circumvallate placenta causing preterm premature rupture of membranes post-amniocentesis (Indian Journal of Case Reports, 2024)
We report a case of circumvallate placenta which led to preterm premature rupture of membranes (PPROM) and leakage in a mother at 17 weeks of gestation. The mother underwent amniocentesis after the triple marker test showed an increased risk for trisomy 21. We encountered difficulty in aspirating amniotic fluid due to the abnormal placental structure, which was not known at the time of the invasive procedure. The mother experienced leaking 7 days post-procedure, followed by miscarriage. Autopsy examination revealed that the placenta was circumvallate, which not only caused difficulty in aspirating the amniotic fluid but also could be the cause of PPROM, a well-known complication of the circumvallate placenta. We emphasize that examining the placenta is very important to identify the cause of events in certain situations; circumvallate placenta or abnormal placenta can be suspected in cases where hindrance is encountered (not able to aspirate amniotic fluid even if the needle is visible in the amniotic sac) during amniocentesis.